Variation in second and heritage languages crosslinguistic perspectives - Bayley, Robert, 1943-; Preston, Dennis Richard; Li, Xiaoshi (Associate professor of Chinese) (Studies in language variation ;, 2022)
"Variationist work in Second Language Acquisition (SLA) began in the mid 1970s and steadily progressed during the 1980s. Much of it was reviewed along with newer approaches in Bayley and Preston 1996 (B&P), heavily devoted to VARBRUL analyses that exposed the variability in developing interlanguages and placed variationist work within the canon of SLA. This new volume features three developing trends. First, it widens the scope of L1s of learners (from 6 in B&P to 8) and L2 targets (2 in B&P to 7) and in each case has brought more careful demographic and variable considerations to bear, including heritage languages and study abroad. Second, it modernizes statistics by moving from VARBRUL to the more widely used log-odds probabilities that allow more detailed consideration of variables and their influences. Finally, it deepens consideration of variable sociolinguistic meaning in learner behaviors, a dominating feature of 3rd Wave variationist work"--